[PP.22.05] HIGH PHOSPHATURIA IS AN INDEPENDENT PREDICTOR OF PROGRESSION OF RENAL DYSFUNCTION IN PATIENTS WITH METABOLIC SYNDROME AND EARLY CHRONIC KIDNEY DISEASE. (September 2016) - Robles, A.; Santamaria, R.; Rodriguez, M.; Aljama, P.
Abstract : Objective: Metabolic syndrome (MS) is linked to increased risk of chronic kidney disease (CKD) by mechanisms not yet established. Experimental data show that high urinary phosphorus excretion (UPE) is related to kidney injury. So far, it is unknown whether high UPE is related to CKD progression in patients with MS. To analyze factors related to CKD progression in patients with MS, focusing on UPE, independently of previously known factors. Design and method: Retrospective case-control study. Patients with MS and early CKD regularly followed in a Hypertension Center. Inclusion criteria: 18–80 years-old, MS defined by International Diabetes Federation criteria, estimated glomerular filtration rate (eGFR) 30–90 ml/min/1.73m 2, urinary albumin to creatinine ratio (A/Cr) < 0, 4 mg/mg. Exclusion criteria: known primary renal diseases as cause of CKD. Demographic variables, comorbidity, medication use, blood and urine biochemical variables were collected from a database. The slope of eGFR (seGFR) change during the follow-up was calculated using first and last eGFR and follow-up time. Patients with seGFR lower or higher than median value were classified as progressors (PRO) or non-progressors (NON-PRO) respectively. The prediction of PRO condition was considered as primary aim. Univariate analysis was performed to identify factors related to PRO condition. Multivariate analysis adjusted for relevant variables. Results: 95 patients were included, age 63, 08 ± 11, 54 years-old (mean value ± standard deviation), eGFR 62, 11 ± 19, 09 ml/min/1.73m2, A/Cr 0, 05 ± 0, 08 mg/mg, follow-up of 2.71 ± 1.61 years. In the univariante analysis, a higher urinary P excretion measured by urinary P to creatinine ratio (P/Cr) in the first morning void was found in PRO vs NON-PRO (0, 66 ± 0, 18 vs 0, 57 ± 0, 16 respectively, p = 0, 012). No other significant differences were found. A correlation P/Cr and seGFR was observed. In multivariate analysis baseline eGFR, systolic blood pressure and P/Cr were independently associated with seGFR. P/Cr and A/Cr were independent predictors of PRO condition. Conclusions: High urinary P excretion is associated with decline in GFR and CKD progression in patients with MS and early stages of CKD independently of previously known CKD progression related factors.